2017
DOI: 10.29252/ijrm.15.8.491
|View full text |Cite
|
Sign up to set email alerts
|

Association of SNP rs.2414096 CYP19 gene with polycystic ovarian syndrome in Iranian women

Abstract: Background: Genetic factors are believed to play an important role in the etiology of polycystic ovarian syndrome (PCOS) which is the most common endocrinological disorder of women in their reproductive age. Androgen metabolism is impaired in PCOS and, thus, CYP19 gene which is involved in this pathway can be a candidate gene. Previous studies have shown a relationship between single nucleotide polymorphism (SNP) of CYP19 in hyperandrogenism and PCOS in some racial groups. Objective: This study was designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Our results are in accordance with the case–control study carried out by Jia et al, on 684 individuals consisting of 386 PCOS women and 298 controls who reported increased frequency of the mutant homozygous genotype (AA) in non-PCOS women over the PCOS patients suggesting protective nature in Chinese population 13 . Similar to our results, a study by Hemini et al, and Mehdizadeh et al, also found a significant variation in genotypic and allelic frequencies in SNP rs.2414096 of CYP19 between the case and control groups and concluded that this SNP is associated with the pathogenesis of PCOS 15 , 16 . Similar results were observed by Mutib et al, who reported a positive association of rs2414096 polymorphism of CYP19 gene with hyperandrogenism and PCOS in Iraqi women 17 .…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in accordance with the case–control study carried out by Jia et al, on 684 individuals consisting of 386 PCOS women and 298 controls who reported increased frequency of the mutant homozygous genotype (AA) in non-PCOS women over the PCOS patients suggesting protective nature in Chinese population 13 . Similar to our results, a study by Hemini et al, and Mehdizadeh et al, also found a significant variation in genotypic and allelic frequencies in SNP rs.2414096 of CYP19 between the case and control groups and concluded that this SNP is associated with the pathogenesis of PCOS 15 , 16 . Similar results were observed by Mutib et al, who reported a positive association of rs2414096 polymorphism of CYP19 gene with hyperandrogenism and PCOS in Iraqi women 17 .…”
Section: Discussionsupporting
confidence: 92%
“…Studies also revealed an association between an SNP of the CYP19 gene in hyperandrogenism and PCOS in some ethnic groups. The studies further stated that among Iranian women, variants of SNP rs.2414096 in CYP19 could be responsible for the occurrence of PCOS (40). All these studies clearly suggest the role of genetic factors in the appearance of PCOS.…”
Section: Resultsmentioning
confidence: 94%
“…The genetic risk calculated by GWAS studies was significantly connected with PCOS and associated clinical features (39). There is a report that indicated that androgen metabolism was deteriorated in women with PCOS, thus the CYP19 gene, which is associated in this pathway, can be a novel gene for investigation (40). Studies also revealed an association between an SNP of the CYP19 gene in hyperandrogenism and PCOS in some ethnic groups.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, this consensus sequence includes R264 in human aromatase that is mutated into a Cys or His in some polymorphisms that are also reported to alter aromatase activity when used in combination with polymorphic variants of CPR [ 66 ]. Moreover, they have been associated with an increased risk for estrogen-dependent pathologies such as breast cancer and polycystic ovary syndrome [ 67 , 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%